Passive limb movement test facilitates subthalamic deep brain stimulation under general anesthesia without influencing awareness - Sheng-Tzung Tsai; Shee-Ping Chen; Sheng-Huang Lin; Shinn-Zong Lin; Shin-Yuan Chen (Tzu Chi Medical Journal)
Objectives: We have shown that neuronal activity in the subthalamic nucleus (STN) in patients with Parkinson's disease can be accurately recorded during deep brain stimulation (DBS) with general anesthesia (GA). However, a vigorous passive range of motion (PROM) test might exert awakening effects on patients who are lightly anesthetized. We will explore the effects of PROM on the heart rate (HR) and mean arterial pressure (MAP) during microelectrode recording (MER) and confirm whether it facilitates identifying the sensory motor portion of the STN under GA. Materials and Methods: 3T magnetic resonance image targeting of the STN was done to guide MER during frame-based stereotactic procedures for DBS. Regular induction and endotracheal intubation for GA were performed and then maintained with a volatile anesthetic agent and muscle relaxant only. The depth of anesthesia was monitored by the bispectral index (BIS). Results: A total of ten patients were enrolled in this study. Their mean age was 48.5 ± 10.8 years old with a disease duration 8.6 ± 2.4 years at the time of surgery. During MER, PROM significantly decreased recording tract numbers and still reached the STN at a recorded length at 5.5 ± 0.8 mm. Compared with baseline, PROM increased HR by a mean 0.5 beats/min and MAP by a mean 1.4 mmHg (P = 0.1178 and 0.0525). The change in BIS was −0.7 (P = 0.4941), and the mean alveolar concentration of the anesthetic agent changed little throughout surgery. Conclusions: PROM was effective in triggering and magnifying neuronal firing signal without influencing patient awareness during MER for STN-DBS under GA.